Strategi Pengembangan Ekonomi Masyarakat Berbasis Wisata Di Wilayah Makam Bung Karno (Studi di Kelurahan Sentul Kota Blitar) - Didik Setiawan (Universitas Islam Kadiri, 2020)
This research is done to know district development Strategy Wahrlimo as area of economy gets wisata's basis analisis's method that is utilized on this research is Analisis SWOT( Strenght, Weakness, Opportunity, Threath). Of this research result points out that main strategy that shall be done to be able to render wisata's area at Makam BungKarno district as ekowisata's area religi is divided as three main strategies, which is: Territorial settlement with form zonasi's system to wisata's activig' and fishery activity that done by society. Beaches promotion step-up Makam Bung Karno comprises to arrange wisata's program culturizes. Counselling about the importance for pelestarian environmentally, tacling act of god and sacrilege danger.